Problem-solving cases in Microsoft Access and Excel - Monk, Ellen F.; Brady, Joseph A. (Course Technology, 2016)
Helps you effectively apply the Access database management system and Excel spreadsheet to analyze and solve real-world business problems. In this title, six tutorials build your practical knowledge of each software application's capabilities, while 12 all-new case studies present scenarios and problems common in today's business practice